2021
DOI: 10.3390/plants10061181
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins from Rubus fruticosus L. and Morus nigra L. Applied as Food Colorants: A Natural Alternative

Abstract: Given the importance of colour in the general acceptance or rejection of a product, the use of colorants is a widespread practice, particularly in the food industry. At the same time, with the increasing consumers’ awareness of the health effects that some artificial colorants can exert, there is a growing tendency to prioritize foodstuffs containing natural additives. In this work, Morus nigra L. and Rubus fruticosus L. fruit juices were characterized in terms of anthocyanins, organic acids, free sugars, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Numerous anthocyanins have been identified in raspberry fruits, mainly cyanidin derivatives (sophoroside, glucoside, rutinoside as well as diglucosides) and pelargonidin [ 38 , 39 , 40 ]. Blackberries are also dominated by cyanidin glycosides [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous anthocyanins have been identified in raspberry fruits, mainly cyanidin derivatives (sophoroside, glucoside, rutinoside as well as diglucosides) and pelargonidin [ 38 , 39 , 40 ]. Blackberries are also dominated by cyanidin glycosides [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…After harvesting, their aroma and appearance change, decomposition processes increase, and synthesis processes are reduced in intensity, which is why an optimal method of preservation is recommended [172,174]. In order to satisfy the requirements of consumers by ensuring that products are both healthy and delicious, and since mulberries are famous all over the world, they have started to be processed in different forms, so that they can be stored and consumed in the long term [172,175,176]. Due to the anthocyanin pigments responsible for their dark color, mulberry fruits are also used as color or flavor additives in the food industry for the production of healthy foods without synthetic food additives [165,176].…”
Section: Applications Of Mulberry In the Food Industrymentioning
confidence: 99%
“…The water-soluble anthocyanin pigments responsible for the color of mulberry fruits are also used as color or flavoring additives in the food industry, a practice increasingly used to create foods that contain natural additives [165,176].…”
Section: Applications Of Mulberry In the Food Industrymentioning
confidence: 99%
“…Blackberry ( Rubus fruticosus ) belonging to Rosaceae family is enriched in phenolic compounds mostly flavonoids including flavonols, ACNs, and ellagitannins [ 73 ]. It has previously been reported that this fruit due to the presence of these phenolics, is a potent natural agent for the treatment of the age-related neurodegenerative diseases, apart from its high antioxidant effect [ 74 ].…”
Section: Anti-prostate Cancer Properties Of Anthocyanidins/anthocyaninsmentioning
confidence: 99%